Distribution of intestinal metaplasia as a predictor of gastric cancer development. Issue 8 (August 2015) - Shichijo, Satoki; Hirata, Yoshihiro; Sakitani, Kosuke; Yamamoto, Shinzo; Serizawa, Takako; Niikura, Ryota; Watabe, Hirotsugu; Yoshida, Shuntaro; Yamada, Atsuo; Yamaji, Yutaka; Ushiku, Tetsuo; Fukayama, Masashi; et al.
Abstract Background and Aim H elicobacter pylori, gastritis, and intestinal metaplasia (IM) are known risk factors for gastric cancer. In the present study, we conducted a cohort study to evaluate the predictive value of the distribution of IM for gastric cancer development. Methods We conducted a retrospective cohort study at a university hospital. From June 1998 to December 2000, we assessed histological gastritis using biopsy specimens, one from the antrum and one from the corpus, from 1450 patients, among whom 729 revisited for follow‐up endoscopy. Patients were classified into three groups according to the distribution of IM at initial endoscopy. IM group A had no IM, IM group B had IM in the antrum only, and IM group C had IM in the corpus. The development of gastric cancer was assessed by endoscopic examination. Results The mean duration of follow‐up was 6.7 ± 4.7 years. The cumulative incidence of gastric cancer at 5 years was 1.5% in total and 0.8%, 3.3%, and 2.7% in IM groups A, B, and C, respectively. The IM group was identified as an independent risk factor by multivariate analysis; compared with IM group A, hazard ratios were 3.6 (95% confidence interval [CI] 1.1–12.1) in IM group B and 3.8 (95% CI 1.01–14.1) in IM group C. In IM group C, the incidence of gastric cancer in patients who received eradication therapy was significantly lower than that in patients who did not receive (P = 0.021, log‐rank). Conclusion IM is a good predictive marker for the development of gastric cancer.